2020
DOI: 10.1111/jrh.12511
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Death Rates Are Higher in Rural Counties With Larger Shares of Blacks and Hispanics

Abstract: This study compared the average daily increase in COVID-19 mortality rates by county racial/ethnic composition (percent non-Hispanic Black and percent Hispanic) among US rural counties. Methods: COVID-19 daily death counts for 1,976 US nonmetropolitan counties for the period March 2-July 26, 2020, were extracted from USAFacts and merged with county-level American Community Survey and Area Health Resource File data. Covariates included county percent poverty, age composition, adjacency to a metropolitan county,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 22 publications
3
109
1
3
Order By: Relevance
“…Figure 3 elucidates that rural counties in the panhandle and southern part of Texas, the western part of New Mexico, Louisiana, Mississippi, Alabama, and Georgia, South Carolina, South of Illinois, and North of South Virginia have significant hotspots of COVID-19 CFR compared to some rural counties in Colorado and California. Most of these counties also have a significant proportion of BIPOC, which aligns with another study that indicates that COVID-19 deaths are higher in rural counties with a higher share of Black and Hispanic populations [ 11 ]. The significant hotspot could be attributed to some of the determinants of health, such as poor access to medical and socioeconomic resources.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Figure 3 elucidates that rural counties in the panhandle and southern part of Texas, the western part of New Mexico, Louisiana, Mississippi, Alabama, and Georgia, South Carolina, South of Illinois, and North of South Virginia have significant hotspots of COVID-19 CFR compared to some rural counties in Colorado and California. Most of these counties also have a significant proportion of BIPOC, which aligns with another study that indicates that COVID-19 deaths are higher in rural counties with a higher share of Black and Hispanic populations [ 11 ]. The significant hotspot could be attributed to some of the determinants of health, such as poor access to medical and socioeconomic resources.…”
Section: Discussionsupporting
confidence: 86%
“…Since the disease outbreak, several attempts have been made to investigate factors driving the variability of COVID-19 infection, mortality rate, and CFR at different geographic scales using different approaches [ 11 , 21 – 25 ]. A multicountry study shows that the political regime, economic parameters, chronic health conditions, behavioral factors (e.g., smoking), and demography are associated with CFR variation among countries [ 22 ].…”
Section: Determinants Of Covid-19 Disparitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an investigation of racial disparity in pregnancy outcomes at a tertiary care medical center found that while black women were more likely, compared to whites, to remain in the hospital for > 4 days, have higher rates of preterm birth, small-for-gestationalage infants, preeclampsia, and stillbirths, hispanic women were found to have lower odds for preterm birth and when compared to black women, hispanic women were less likely to experience any adverse pregnancy events, with the exception of gestational diabetes mellitus. 46 Here, we refer to the Hispanic paradox; the positive health outcomes observed among Hispanic populations despite risks associated with lower SES 47 as a likely explanation while acknowledging that other COVID-19 studies have reported adverse effects in Hispanic populations 48 in general but not among pregnant women in particular. 25 Given that advanced maternal age has been associated with a host of adverse pregnancy outcomes our ndings highlight the need for providers to pay close attention to pregnant women of advanced ages who contract COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Black Americans often live in dense urban environments that can increase exposure to COVID-19 (Adhikari et al, 2020; Kirby, 2020; Stokes et al, 2021). Other studies have tied COVID-19 racial disparities to differences in access to care, economic status, chronic comorbidities, and “essential worker” categorization (Cheng et al, 2020; Paul et al, 2020; Wright et al, 2020). These studies primarily correlate the racial make-up of the population to total COVID-19 mortality, rather than disaggregated mortality data by race.…”
Section: Introductionmentioning
confidence: 99%